Monitoring depth of anesthesia: from consciousness to nociception. A window on subcortical brain activity. Issue 1 (20th November 2014) - Constant, Isabelle; Sabourdin, Nada; Morton, Neil
Summary Anesthesia results from several inhibitor processes, which interact to lead to loss of consciousness, amnesia, immobility, and analgesia. The anesthetic agents act on the whole brain, the cortical and subcortical areas according to their receptor targets. The conscious processes are rather integrated at the level of the cortical neuronal network, while the nonconscious processes such as the nociception or implicit memory require subcortical processing. A reliable and meaningful monitoring of depth of anesthesia should provide assessment of these different processes. Besides the EEG monitoring which gives mainly information on cortical anesthetic effects, it would be relevant to have also a subcortical feedback allowing an assessment of nociception. Several devices have been proposed in this last decade, to give us an idea of the analgesia/nociception balance. Up to now, most of them are based on the assessment of the autonomic response to noxious stimulation. Among the emerging clinical devices, we can mention those which assess vascular sympathetic response (skin conductance), cardiac and vascular sympathetic response (surgical pleth index), parasympathetic cardiac response (analgesia nociception index), and finally the pupillometry which is based on the assessment of the pupillary reflex dilatation induced by nociceptive stimulations. Basically, the skin conductance might be the most adapted to assess the stress in the awake or sedated neonate, while the performances of this method appear disappointing under anesthesia. The surgical pleth index is still poorly investigated in children. The analgesia nociception index showed promising results in adults, which have to be confirmed, especially in children and in infants, and lastly pupillometry, which can be considered as reliable and reactive in children as in adults, but which is still sometimes complicated in its use.